Major Concerns? A Longitudinal Analysis of Student- Athletes’ Academic Majors in Comparative Perspective - Sanders, James P.; Hildenbrand, Kasee (Journal of Intercollegiate Sport, 2010)
This paper investigates the over-representation of student-athletes in academic majors, a pattern known as clustering. Three issues are examined. The first is whether clustering occurs at college entrance or later. The second is whether some athletes are at extra risk of clustering. The third is whether clustering contributes to future income inequalities. Analyses of a major university’s student records revealed that athletes clustered at the start of college but the tendency to do so was moderated by race, sex, and type of sport played. Clustering also intensified greatly over time, particularly for African American athletes. By the eighth semester, 64% of African American athletes were social science majors. In the short-term, clustering lowered athletes’ projected incomes, but long-term income projections based on academic major slightly favored groups of athletes who clustered within the social sciences.